Aggression As a Predictor of General Well-Being Among Public Health Workers - Anurekha K Tharumiya; Preetha Menon; Manikandan MK Manicka; Nandhini C (ACHSM, 2022)
Social atrocities and discrimination make sanitary workers vulnerable to aggression which in turn disrupts their well-being. The issues concerning the psychological health of sanitary workers have been addressed less by researchers. The present study aimed to assess the level of aggression and general well-being among sanitary workers. An aggression questionnaire, consisting of four dimensions, namely physical aggression, verbal aggression, anger and hostility was used. The PGI general well-being measure and personal profile sheet consisting of socio-demographic details was given to 150 sanitary workers who were selected through purposive sampling method. The dimensions of aggression- anger and hostility were negatively correlated with the general well-being of the participants. Amongst the four dimensions of aggression, anger is found to be the predictor of general well-being.